A IMPLEMENTASI KEGIATAN PEMBIASAAN PAGI DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA DI MAN 1 JOMBANG: IMPLEMENTASI KEGIATAN PEMBIASAAN PAGI DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA DI MAN 1 JOMBANG - Mei Linda, Laela; Said, Ali (Al Tadib : Jurnal Ilmu Pendidikan, 2025)
By habituation, this means that repetition activities are carried out so that the repetition activity is not forgotten and will continue to become a habit for students. MAN 1 Jombang implements habituation activities by carrying out morning habituation activities such as dhuha prayers in congregation, reading asmaul husna, and tadarus Al-Qur'an, and so on to improve students' religious character. The focus of this research is: 1) How does the implementation of morning habituation activities improve the religious character of students at MAN 1 Jombang? 2) What are the supporting and inhibiting factors for morning habituation activities in improving the religious character of students at MAN 1 Jombang? The approach used in this research is a qualitative approach with the type of research used is case study research. The data collection techniques used were observation, interviews and documentation. The results of this research are as follows: 1) The form of implementation of morning habituation activities in improving the religious character of students at MAN 1 Jombang is by getting used to worship and learning good things. The belief is instilled in students to obey and submit in carrying out the commands of Allah SWT, to carry out worship in accordance with religious law as a Muslim's obligation. 2) Supporting factors and inhibiting factors for morning habituation activities in improving the religious character of students at MAN 1 Jombang are supporting factors, namely support in the form of equipment or facilities, facilities and policies from the madrasa head, the competence of educators at MAN 1 Jombang, self-awareness of each students, madrasas that prioritize religious character and strong religious awareness. Meanwhile, the inhibiting factors are internal problems that teachers and students have, a feeling of laziness that grows within students, and students who lack discipline in leaving early in the morning.